Memahami Hermeneutika dalam Mengkaji teks Al-Qurâan - Fitria, Rini (UIN Antasari Banjarmasin, 2016)
Fakultas Ushuluddin Adab dan Dakwah IAIN BengkuluThis paper contains about how to understand that critical hermeneutics originally began the study of philosophy towards the understanding of science communication or broadcast communication texts of Islam to understand the Quran. Theoretical, philosophical hermeneutics and critical hermeneutics is the science of how to interpret the meaning in the text with the study of the initiators, the reader and the context at the time. Al-Quran is a holy book that can be understood by assuming the critical hermeneutics, the word of Allah is understood by the readers of these words by looking asbabunnuzulul Quran.Keywords: hermenutika, Quran, initiators, reader and context